Enhancing EFL Prospective Teachers' Classroom Management Skills Through the implementation of Flipped Classroom - Ramadan, Israa (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2022)
Numerous endeavours have been detected to improve new techniques, strategies, and methods for enhancing teachers' classroom management skills, both in the pre-service and in-service settings. This study aimed at investigating the effectiveness of using the flipped classroom model in developing Egyptian EFL prospective teachers' classroom management skills. This study adopted the experimental research design that has been exploited in the current study. The sample of the study consists of 34 EFL prospective teachers in Hurghada Faculty of Education, South Valley University, Egypt. The researcher has designed and validated a classroom management questionnaire to be used for data collection purposes. There are statistically significant differences in the mean scores of the experimental and control groups' in providing an atmosphere of classroom discipline in favor of the experimental group in the post-testing in providing an atmosphere of classroom discipline (Mexperimental = 60.88, Mcontrol = 46.29), Stirring pupils' motivation to learn (Mexperimental = 62.94, Mcontrol = 47.58), Regulating the process of classroom interaction (Mexperimental = 71.64, Mcontrol = 55.17), classroom management skills (Mexperimental = 195.47, Mcontrol = 149.06). Therefore, the present study highlighted that the flipped classroom model had a significant effect on developing some classroom management skills of Egyptian EFL prospective teachers. It is recommended that more research is needed to test flipped classroom teaching models for language skills such as listening, speaking, reading, writing, vocabulary, and grammar.